Predicting short message service (SMS) usage among university students using the technology acceptance model (TAM) - Ramayah, T.; --, Yulihasri; Ibrahim, Amlus; Jamaludin, Norzalila (2006)
This paper uses the Technology Acceptance Model (Davis, 1989) to predict SMS usage amongst university students who form the biggest user of this service.TAM proposes that two constructs ie; perceived ease of use and perceived usefulness will influence the acceptance of a technology. Data was collected from 90 students from a public university with the use of a structured self-administered questionnaire. The findings of the study indicate that both perceived ease of use (β=0.191, p<0.05) and perceived usefulness (β=0.276, p<0.01) are positively related to usage. Furthermore, it was found that the impact of perceived ease of use on usage is partially mediated by perceived usefulness.Perceived usefulness was more influential in predicting usage as compared to ease of use.Thus it can be concluded that the use of SMS is influenced to a larger extent by the utility of the service and to a lesser extent the ease of use of the service.